The impact of activated charcoal and graphite on growth parameters and production of secondary metabolites of Plantago maritima through in vitro culture - Fatemeh Najafi; Samin Mohammadi; Parina Asgharian; Morteza Kosari-Nasab (BMC Chemistry)
Abstract Plantago maritima L. is a highly adaptable species recognized for producing valuable secondary metabolites with significant medicinal properties and a broad geographical distribution. This study explored the effects of various Graphite (G) and Activated Charcoal (AC) concentrations on the growth parameters and secondary metabolite production of P. maritima during the propagation stage. Concentrations of G and AC (0, 2, 4, and 8 g/L) were tested individually, and total phenolic and flavonoid contents were measured using folin-ciocalteu and aluminum chloride reagents, respectively. Antioxidant activity was evaluated using the DPPH assay. Spectroscopic techniques were employed to assess pigment composition, phenolic acid profiles, and n-hexane extracts, utilizing GC-MS and LC-MS/MS. The results indicated that high concentrations of G (4 and 8 g/L) and low concentrations of AC (2 and 4 g/L) significantly influenced growth parameters. A low G concentration (2 g/L) notably enhanced pigment production, while AC treatments at 4 and 8 g/L maximized phenolic content, antioxidant activity, and terpenoid levels. Application of 4 g/L of AC resulted in the production of biologically active rosmarinic acid, a compound not observed in other treatment conditions or the control sample. Overall, the cultivation of P. maritima demonstrates considerable potential for the biosynthesis of bioactive metabolites and promoting growth. However, further investigation into the elicitors’ role and underlying mechanisms is critical to optimize production efficiency.